Pengaruh Penggunaan Strategi Pembelajaran Card Sort Media Gambar Terhadap Hasil Belajar IPS Siswa Kelas V SDN 1 Taruban Nogosari Tahun Ajaran 2015/2016 - Kurniawati, Ariska Etik; , Drs. H Suwarno (2016)
Abstrack Ariska Etik Kurniawati/A510120161. The Effect of Card sort Strategy with media images on learning outcomes IPS. Essay. Faculty of Teacher Training and Education. Muhammadiyah University of Surakarta. March 2016.This study aims to determine the influence is there and how much influence the implementation Card sort strategy with media images of the results of social studies class V SDN 1 Taruban Nogosari Academic Year 2015/2016. This type of research is research experiments. Analysis of data using simple regression test which includes Hypothesis test (t test) and test of determination (r2). With the results of t test analysis between variables Card sort strategy with media images and social studies outcome variable in the experimental class obtained Prob. t X amounted to 0.011 <0.05. Ho rejected. So variable Card sort strategy with media images (X) significantly. The regression coefficient of 1.044 X states that any influence Card sort strategy with media images (X) up 1 unit, the IPS student learning outcomes will increase by 1.044 units. In the test strategy known r2 Card sort with media images influence by 20% for improved learning outcomes IPS. It can be concluded that the Card sort strategy with media images have a great influence on learning outcomes IPS. Keywords: Card sort, media image, learning outcomes.